Upaya Transnasionalisasi Pergerakan Al Qaeda Pasca-11 September 2001 - Wibowo, Prihandono (Global and Policy Journal of International Relations, 2013)
ABSTRACTThis study reveals the reason Al Qaeda can survive and develop global terrorism trend in the post-2001 period. Through the analysis of various Al Qaeda‟s document, the answers obtained. First, Al Qaeda change its ideology from old ideology to new ideology. The old Al Qaeda's ideology limited to discuss about militarism issue and how to expelled U.S. military from the Middle East. While in the new idelogy, Al-Qaeda attempt to attract popular support from the muslim widely. Al Qaeda raise globalization issues that associated with U.S. global imperialism. Second, Al Qaeda use of the means of thriving in globalization. Al Qaeda applying the concept of All-Channel network and utilize information technology for the benefit of the movement. With that combination, al Qaeda succeeded in developing a global movement trendKeywords: globalization, contemporary global issues, popular support, global movements, networks, information technology.DOI:https://doi.org/10.33005/jgp.v1i01.2010